1999
DOI: 10.2135/cropsci1999.3951340x
|View full text |Cite
|
Sign up to set email alerts
|

Limitation to Photosynthesis in Pratylenchus penetrans‐ and Verticillium dahliae‐Infected Potato

Abstract: Mechanism(s) responsible for decrease in photosynthetic rates of potato (Solanum tuberosum L.) leaves infected by the fungus Verticillium dahliae (Kleb) and the nematode Pratylenchus penetrans (Cobb, Sher, Allen) have not been fully researched. Two growth chamber experiments were undertaken to determine the factors contributing to the decrease in CO2 exchange rates of young, fully expanded leaflets of potato (cv. Russet Burbank) plants grown in pots infested with P. penetrans and/or V. dahliae Treatments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…1e), which limited CO 2 supply to the chloroplast. Our results agree with previous studies which demonstrated that, following infection with V. dahliae, photosynthesis of potato and pepper was reduced early as a result of stomatal closure caused by drought stress in leaves (Bowden et al, 1990;Haverkort et al, 1990;Bowden and Rouse, 1991;Saeed et al, 1997Saeed et al, , 1999Goicoechea et al, 2001). By contrast, some authors have reported that other pathogenic mechanisms, apart from water stress, can play a significant role in either decreased photosynthesis or stomatal closure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…1e), which limited CO 2 supply to the chloroplast. Our results agree with previous studies which demonstrated that, following infection with V. dahliae, photosynthesis of potato and pepper was reduced early as a result of stomatal closure caused by drought stress in leaves (Bowden et al, 1990;Haverkort et al, 1990;Bowden and Rouse, 1991;Saeed et al, 1997Saeed et al, , 1999Goicoechea et al, 2001). By contrast, some authors have reported that other pathogenic mechanisms, apart from water stress, can play a significant role in either decreased photosynthesis or stomatal closure.…”
Section: Discussionsupporting
confidence: 92%
“…On the one hand, several authors have proposed that water stress induced by Verticillium infection is a crucial factor to explain the impaired leaf photosynthesis in diseased plants (Bowden et al, 1990;Haverkort et al, 1990;Bowden and Rouse, 1991;Lorenzini et al, 1997;Saeed et al, 1999). In most of these studies, the reduction in net photosynthesis was attributed to stomatal closure, which reduces the concentration of CO 2 within leaves.…”
Section: Introductionmentioning
confidence: 99%
“…This result agrees with data reported for other plant species (Bowden et al 1990;Goicoechea et al 2001;Haverkort et al 1990;Lorenzini et al 1997;Pennypacker et al 1990;Sadras et al 2000;Saeed et al 1999). Vascular wilt pathogens decrease plant hydraulic conductance due to plugging of the xylem vessels by the fungus, which may lead to leaf water deficits (Adams et al 1987).…”
Section: Discussionsupporting
confidence: 91%
“…Such plating methods were used to differentiate among cultivars and breeding lines in the selection for and study of resistance to PED (10,14,17,25-28, 45,62). Those assays were also employed to describe the epidemiology of the disease and colonization by the pathogen under various agricultural and environmental conditions (2)(3)(4)15,16,18,19,24,40,43,48,52,61). Expression of PED symptoms is greatly affected by environmental and agricultural conditions (e.g., weather during the growing season, irrigation frequency, and nitrogen fertilization), and selection of breeding lines based solely on symptoms is generally discouraged.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ground rye seed infested with V. dahliae VCG4A isolate V18 were buried in the furrow with each tuber seed piece at planting (9 May 2005). Isolate V18 is a highly aggressive strain of V. dahliae that was isolated from severely affected potato plants in the same field and was used successfully in numerous studies of PED both in the field and in the greenhouse (2,3,(26)(27)(28)33,43,52).…”
Section: Methodsmentioning
confidence: 99%